Herencia de la precocidad en una poblacion local y varios conjuntos de lineas de maiz - Casañas, F.=700 1 Bosch, Ll.
(Es, En)
ilus., 22 ref.
Keywords: HERENCIA GENETICA; PRECOCIDAD; MAIZ; LINEAS PURAS; VARIEDADES; ESPAÑA